0557 The Effect of Sleeping Position on the Efficacy of Hypoglossal Nerve Stimulation. (12th April 2019) - Chou, Courtney; Poomkonsarn, Sasikarn; Liu, Stanley Y; Capasso, Robson; During, Emmanuel
Abstract: Introduction: While studies have demonstrated hypoglossal nerve stimulation (HNS) to be a safe and overall effective treatment for certain patients with obstructive sleep apnea (OSA), not all who meet current selection criteria respond to therapy. In an effort to elucidate better criteria for patient selection, this study aimed to look at the effect of sleeping position - specifically, supine and non-supine positions - on the efficacy of HNS therapy. Given that the collapsibility of the upper airway is increased in the supine position due to the influence of gravity on the shape and size of the airway, we hypothesized that supine position would correlate with lower HNS efficacy, as measured by apnea-hypopnea index (AHI), as compared to non-supine position. Methods: We performed a chart review of all patients implanted with HNS at Stanford University Medical Center since 2015. Patients with pre- and post-operative in-lab polysomnography (PSG) performed within the institution were included in the study. Baseline and treatment supine AHI and non-supine AHI were measured. Student's paired t-test was used to compare the percent improvement in AHI from baseline to treatment between supine and non-supine positions. Results: Eleven consecutive patients meeting inclusion criteria were selected for this preliminary analysis. Analysis showed a significantly greater mean reduction in non-supine AHI (82.8%) compared to supine AHI (32%) (p = 0.012). Conclusion: Our results suggest that HNS may be less effective in the supine position, supporting the importance of evaluating sleeping position preference during patient selection. This study adds to the growing body of literature investigating elements that may hinder the success of HNS therapy. Support (If Any): N/A